Epidemiologia molecular de isolados de Brucella Abortus de bovinos no Brasil, 2009 a 2013 - Mayra da Silva Oliveira (2016)
The aims of the present study were genotype Brucella abortus strains isolated from cattle in Brazil between 2009 and 2013, and to analyze their distribution to support the Brazilian program on control and eradication of brucellosis. One hundred and forty strains isolated from cattle in Brazil between 2008 and 2013 were genotyped using a set of 18 VNTR (MLVA16 + HOOF-Print 3 + HOOF-Print 4). The analysis of MLVA8 revealed eight different genotypes among B. abortus 9 strains, including five previously described and three new ones. Analysis of the MLVA16 loci revealed fifty-eight distinct genotypes, from which three were identical, thirty-eight were considered very close, and seventeen were considered distant compared to those previously described and deposited in MLVAbank. Analysis of the HOOF-Prints 3 and 4 revealed the larger number of different alleles among all VNTR assessed, exhibiting maximum resolution when associated with MLVA16 markers. Our results validate the usefulness of the MLVA technique, especially MLVA16, in the molecular epidemiology of B. abortus. This study also provides insights on the genotypes of B. abortus circulating in Brazil, which certainly contribute for the better understanding of the epidemiology and control of bovine brucellosis in the country. Moreover, our data showed a high genetic diversity among the B. abortus isolates and a close relationship among these strains and Brazilian B. abortus deposited by MLVAbank, demonstrated by micro-evolutionary divergence arising from mutations in hypervariable loci.